"A pig and a garden": Fannie Lou Hamer and the Freedom Farms Cooperative. Issue 1 (2nd January 2017) - White, Monica M.
ABSTRACT: Much of the scholarship on the work and legacy of activist Fannie Lou Hamer concentrates on her tireless efforts for civil/human rights and African American representation and access to electoral politics. This article brings to light an important project she started in 1969, Freedom Farms Cooperative (FFC) in Sunflower County, MS. An agricultural cooperative built on 680-acres, Freedom Farms included a pig bank, Head Start program, community gardens, commercial kitchen, a garment factory, sewing cooperative, tool bank, and low-income, affordable housing as strategies to support the needs of African Americans who were fired and evicted for exercising the right to vote. Freedom Farms offered these sharecroppers and tenant farmers educational and re-training opportunities including health care and disaster relief for those who wanted to stay in the Mississippi Delta. Using a historical method to analyze extensive archival records, this article offers an analysis of Freedom Farms and illuminates valuable lessons on agriculture as resistance, and alternative strategies of rebuilding and investing in sustainable communities. Using the principles of collective and shared ownership, Freedom Farms and the work of Ms. Hamer, offer us important and valuable lessons on rebuilding our communities and investing in sustainable cities around growing food. This article outlines some of these lessons.